Dynamics of changes in plasma fatty acid binding proteins and intestinal zonulin in patients with generalized intra-abdominal infection and abdominal sepsis depending on the severity of patients - I. A. Kryvoruchko; M. O. Sykal (Клінічна хірургія, 2021)
Objective. Determine the levels of plasma intestinal fatty acid binding proteins levels in combination with zonulin in patients with generalized intra-abdominal infection and abdominal sepsis, and define the clinical usefulness them to assess the severity of patients.